Potensi Micro RNA Hsa-Mir-Let-7b-5p Dalam Peran Insulin Signaling Pathway - Muhammad Kharisma; Mahdea Kasyiva (STIKes Ibnu Sina Ajibarang, 2023)
Insulin plays an important role in metabolism. miR-Let-7b-5p has an important role in the regulation of genes that play a role in the insulin signaling pathway. This study aims to look at the role of hsa-miR-Let-7b-5p in the insulin signaling pathway and the genes related. This research method is an in silico study using DIANA MiRPath v3.0. Pathway analysis was performed using DIANA MiRPath v3.0 web-based software to analyze miRNA regulation. This research uses data on the regulatory pathways of the Homo sapiens species. The results showed that there were 10 target genes from hsa-miR-Let-7b-5p in the insulin signaling pathway. The metabolic processes involved in the insulin signaling pathway are related to glucose uptake, lipogenesis, glycolysis, glycogenensis, antiapoptosis, protein synthesis, proliferation and differentiation. The NRAS, MAP2K2 and KRAS genes affect the process of proliferation, differentiation and protein synthesis. The CRKL gene influences the process of glucose uptake. The ACACA gene influences the process of lipogenesis. The GYS1 gene influences the process of glycogenesis. The PRKAR2A gene influences the antilipolysis process. The INPPL1 gene influences the inhibition of the PI3K gene into aPKC, PDKI2 and mTOR in various pathways in the insulin signaling pathway. Other pathway processes related to the insulin signaling pathway are the phosphatidyl signaling system and the MAPK signaling pathway. So that miR-Let-7b-5p as an indicator of examination or can be a target of therapy related to the role of insulin.